Management tools protocols for organizing the cerebral accident care line: an integrative review (Research, Society and Development, 2021)
Objective: Conduct an integrative literature review about the management tools used in the Stroke Care Line. Methodology: For the articles selection, the following databases were used: LILACS (Latin American Literature in Health Sciences), MEDLINE (National Library of Medicine), SCOPUS - Multidisciplinary database and CINAHL (Cumulative Index of Nursing and Allied Health Literature), in English, Spanish and Portuguese. The research took place from November 2020 to April 2021, using the controlled descriptors in English "Management Decisions" and "stroke", mediated by the Boolean operator "and", aiming to expand the number of studies. The descriptors were extracted from the DECS (Health Sciences Descriptors) of the BVS Portal, the MESH (Medical Subject Headings) of the National Library, and the CAPES / MEC Journal Portal. Results: Education technologies were the most found in the literature compared to innovative technologies, such as: pamphlets, booklets and lectures, showing relevance for facing the patient and the community, contributing to the early identification of the first signs and symptoms, which can still be considered a challenge in this work. Conclusion: It is possible to improve the quality of life of stroke patients through the existence of managerial technology tools that guarantee a fast and effective communication between the multidisciplinary team and the management of health services.